LANDSHAFTLARDAN FOYDALANISHDA TURLI YONDASHUVLARNING QO‘LLANILISHI - Xasanov, P.A. (SCIENCE and SOCIETY, 2025)
The article talks about landscapes and its diversity, as well as prospects for its use. Also, the role, fundamental and practical importance of the landscape in the system of geographical knowledge is analyzed, and the main methods are emphasized of determining the specific aspects of the approaches to the use of landscapes.
Keywords: landscapes; approach; use; anthropogenic; theoretical; environmental; ecological; methods